PENGARUH MEDIA POSTER TERHADAP MINAT BELAJAR PADA MATA PELAJARAN IPA SISWA SDN TATAH BANGKAL - Mahrita; Saidah Tunnoor (Yayasan Pendidikan Literasi Borneo, 2025)
The purpose of this research is to determine the influence of poster media on students’ learning interest in Science subjects at SDN Tatah Bangkal. The method employed is an experimental study with a quantitative approach. The object of this research is the effect of poster media on students’ learning interest in Science subjects at SDN Tatah Bangkal, while the subjects are fourth and fifth-grade students. The research sample consists of students from grades IV and V at SDN Tatah Bangkal. The instruments used in this study include questionnaires, observations, and documentation to measure students’ learning interest in relation to the use of poster media in Science subjects. Based on the results of descriptive analysis, the variable of poster media in Science subjects at SDN Tatah Bangkal falls into the “good” category with a score percentage of 80.76%. Meanwhile, the variable of learning interest in Science subjects is categorized as “very good” with a score percentage of 83.96%. Furthermore, the results of simple linear regression analysis show an R square value of 42.6%, indicating that students’ learning interest is influenced by poster media by 42.6%, while the remaining 57.4% is influenced by other factors.